Exploitation of Street Children as Beggars in Deli Serdang: Legal Review and Siyasah Dusturiyah - Safinda, Qory; Syam, Syafruddin (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
Exploitation of street children is a crime that often occurs recently, many street children lose their freedom and do not have adequate protection from their family, region or government. With the existence of laws regarding the protection of children and women and related organizations, it is believed that the number of exploitation cases will decrease, children will receive clear legal protection and can be implemented by state authorities to increase protection for children, especially street children. This research uses a juridically valid and experimental methodology. The aim of this research is to find out efforts to handle and protect street children as victims of exploitation from Deli Serdang Regency regional regulations No.5 of 2021 and how Islam views in handling cases of exploitation of street children which are studied from siyasah dusturiyah